Inovasi Penilaian Pembelajaran Bahasa Arab Berbasis Games KAHOOT untuk Meningkatkan Keterampilan Menyimak di Ma`had IIT Rabbani Bengkulu - Suharsono; M. Ja'far Shodiq; Yusuf Muhtarom (Mahira: Journal of Arabic Studies & Teaching, 2023)
The lack of effectiveness of teacher assessment medium utilized in classroom learning sparked this research. In today's world, learning cannot be isolated from evaluation and assessment. Several assessment-related media have evolved as a result of changing times and the advancement of existing technical capabilities. The goal of this research is to look into KAHOOT media games as an innovation in assessing Arabic language acquisition. The literature method was used in this investigation. According to the findings of this study, KAHOOT is the answer to all of today's sophistication. The use of KAHOOT media in Arabic language instruction at Ma'had IIT Rabbani Bengkulu has a favorable effect on students and increases their motivation to study Arabic more actively. It is intended that this post will serve as an alternative option for assessing learning, particularly Arabic learning.